Reformulasi Sistem Penilaian Kinerja - Eris Yustiono (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2018)
Performance appraisal is an important process dealing with the performance measurement of employees. The result of performance appraisal is significant in human resource management functions. It can be used as a basis to determine the proper compensation, training and development involvement, career management, and other personnel substances. However, based on experience, the tool recently used to measure the employees’ performance, called DP-3, is not an appropriate instrument. The possibility of making mistakes in judging the employees’ performance is quite open, so it may not show an objective performance. Therefore, another approach to measure employees’ performance have to be developed.